PENGARUH DUKUNGAN KELUARGA DAN EFIKASI DIRI TERHADAP WORK LIFE BALANCE KARYAWAN GENERASI MILENIA - Yusuf, Muhammad (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to determine the influence of family support and self-efficacy on the work life balance of millennial generation employees. The approach used in the research is an associative approach. The population in the study was 100 employees with a sample of 50 millennial generation employees. The data collection techniques used were observation, questionnaires and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test, and F test which were processed using the Statistical Product and Service Solution (SPSS) program. The results of the study showed that Family Support (X1) has a significant effect on Work Life Balance. Self-Efficacy (X2) influences Work Life Balance. And Family Support (X1) and Self-Efficacy (X2) simultaneously influence the Work Life Balance of Millennial Generation Employees.